Study on Deflection of Surrounding Rock Force Chain and Disaster Mechanism of Instability in Deep Stope - Guang-Xiang Xie; Anying Yuan; Lei Wang (Shock and Vibration)
The mechanism of force chain deflection and instability-caused disaster in the deep surrounding rock of large-scale stopes was examined in this study using theoretical analyses, laboratory experiments, PFC3D numerical simulations, and other comprehensive research methods based on a discrete element theory that included force chain research as the main line. The results indicated that the overburden strata of the stope presented an arched force chain in both the strike and the inclined direction of the working face. In addition, a force chain shell composed of strong chains similar to “ellipsoid” in shape had been formed in the overburden strata space of the entire stope. The main mechanical characteristics of the force chain shell were as follows: the strength levels of the force chains within the shell were the largest; the strength levels of the force chains inside and outside the shell were relatively low and had evolved with the advancement of the working face; the directions of the force chains in different areas of the surrounding rock masses of the stope were deflected, forming an anisotropic characteristic with a certain deflection angle which was distributed in the vertical direction at the shell base; the force chains at the shell shoulder were angled in the horizontal direction, and the force chain at the shell top had an obvious horizontal direction; finally, the strong chain clusters of the surrounding rock masses of the stope formed a force chain shell in the stope space, and the stress shell was the macroscopic embodiment of the force transference in the force chain shell formed by the force chain clusters, which revealed not only the mechanical mechanism of the force chain shell formed by the surrounding rock but also the relationship between the macro stress shell and the stress chain shell. The stability of the shell determines the stability of the surrounding rock, and the instability of the shell will lead to dynamic disasters such as strong dynamic pressure or rock burst.